Early changes in peripheral blood cytokine levels after the treatment of metastatic hepatic carcinoma with CalliSpheres microspheres drug-eluting beads transcatheter arterial chemoembolization - Liu, Ying; Liu, Song; Zhao, Guang Sheng; Li, Xiang; Gao, Fei; Ren, Zhi Zhong; Bian, Jie; Wu, Jian Lin; Zhang, Yue Wei (Frontiers in Oncology, 2022)
Objective To observe the early changes in peripheral blood cytokine levels after treatment of metastatic hepatic carcinoma (MHC) with CalliSpheres microspheres drug-eluting beads (DEB) transcatheter arterial chemoembolization (CSM-TACE). Methods Twenty-eight patients with refractory MHC who underwent CSM-TACE were selected prospectively, and 5mL of peripheral blood was collected before CSM-TACE and on the 2nd and 5th day after CSM-TACE. Flow cytometry was used to detect immunological indicators. The early changes in levels of peripheral blood cell inflammatory factors Th1 (interleukin 2 (IL-2), tumor necrosis factor-α (TNF-a), interferon (IFN-r)), Th2 (IL-4, IL-6, IL-10), and Th17 (IL-17A) were observed after CSM-TACE, as well as the ratio of CD4+/CD8+. Results All the 28 patients underwent CSM-TACE successfully. CT at 4 days after CSM-TACE showed clear outline low-density changes in liver tumors, and honeycomb necrosis was observed in the tumors in some cases. After CSM-TACE, the IL-6 and IL-10 levels were increased and then decreased again. After CSM-TACE, IL-2 showed a trend of transient increase and then decreased again, and the TNF-a level decreased temporarily, and then decreased. After CSM-TACE, the IFN-r level showed a continuous and slowly increasing trend. The IL-17 level showed a continuous downward trend, and the CD4+/CD8+ ratio showed a gradual and continuous upward trend, and there was a negative correlation between them. Conclusions There are complex dynamic changes in TH1/Th2 in the early stage of CSM-TACE, and the acute inflammatory response and the enhancement of the body’s immune anti-tumor response coexist.